Resource diversity mitigates the effects of intraspecific competition in co-occurring cryptic nematode species - Guden, Rodgee Mae; Derycke, Sofie; Moens, Tom (Frontiers in Marine Science, 2024)
Intraspecific competition and resource diversity are considered major drivers of niche differentiation, which are expected to promote population niche expansion by driving individuals to feed on alternative resources and/or by enhancing individual diet specialization. Nevertheless, experimental studies on the interaction effects of both factors on animal behavior and population dynamics remain scant. Here, we investigate how resource diversity alters the impact of intraspecific competition on resource preference and fitness of three co-occurring cryptic species of the marine nematode complex Litoditis marina (Pm I, Pm III and Pm IV). For each cryptic species, two competition regimes (‘low nematode density’ and ‘high nematode density’) were established in microcosms with varying resource diversity (E. coli, low-, medium- and high- diversity food). Our results show differences in resource preference and population fitness depending on intraspecific competition and resource diversity, but the response also varied considerably between cryptic species. Pm III did not exhibit resource preference under low intraspecific competition, but preferred the two most diverse food sources under high intraspecific competition. Pm IV also showed preference for medium-diversity food under high competition, whereas no resource preference was observed in Pm I regardless of competition regimes and resource diversity. Nevertheless, all cryptic species exhibited enhanced adult population growth on a more diverse food source under stronger intraspecific competition. These results indicate that resource diversity can alleviate intraspecific competition and affect niche diversification, which may impact diversity maintenance in ecological communities.